Future airport expansion at Stansted , Heathrow and Gatwick: Statistics and methodology - Brooker, Peter (Institute of Acoustics, 2004)
Chapter 11 of the Government White Paper 1, the Future of Air Transport, covers the South East of England, and Chapter 11 of the same document discusses Environmental Impacts. The major potential development options recommended are at Stansted, Heathrow and Gatwick. This paper examines the way that the aircraft noise exposure implications of these options was described in the White Paper, stressing statistical and methodological aspects. The presentation and description of quantitative results and aircraft noise assessments needs to be of a high professional standard. It must be noted at the outset that this critique should not be taken as questioning the sincerity of Department for Transport (DfT) officials or their consultants: the work programme and processes that led up to the White Paper were extensive and the technical tasks were formidable. Paragraph numbers and text shown in bold italic below are from the White Paper.